A Pentecostal Lex Legendi For Fostering Polyphonic Perspectivalism in Pentecostal Tradition (Asosiasi Teolog Indonesia, 2013)
I begin this paper by surveying qualitative distinctives of Pentecostal Bible reading, which together contribute to the missional localizing giftedness of Pentecostalism worldwide. In Part 2 I then suggest that detrimentally incongruent to these distinctives are several Fundamentalist-Evangelical mediated postures to Scripture. In Part 3 I address this incongruence by proposing a Pentecostal lex legendi (“rule of reading”), built on Telford Work’s “Trinitarian-Ontology of Scripture.” I argue that Work’s bibliology provides a compelling theological premise for both the Pentecostal dynamic and polyvalent understanding of biblical revelation, and substantiates theological pluralism as intrinsic to Pentecostal tradition. Further building on Work’s bibliology, I then propose a Pentecostal form of lectio divina (“sacred reading”) that structures the classical/medieval fourfold Scripture sense, to a constructivist understanding of the threefold Pentecostal soteriological experiences (redemption, sanctification, and Spirit baptism). I conclude by delineating how this Pentecostal form of lectio divina may help Pentecostals identify and utilize theological hermeneutics that best foster the Pentecostal missiological giftedness, and hence the pluralizing of Pentecostalism(s) worldwide.